2022
DOI: 10.3390/ijerph19010526
|View full text |Cite
|
Sign up to set email alerts
|

How Does Toddlers’ Engagement in Literacy Activities Influence Their Language Abilities?

Abstract: The most intensive period of language development is during the first years of life, during which the brain is developing rapidly. Research has shown that children from disadvantaged households who received high-quality stimulation at a young age grew into adults who earned an average of 25% more than those who did not receive these interventions. In addition, it has been suggested that children who show a greater interest in literacy-related activities and voluntarily engage in them are likely to become bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Altogether, the literature indicates that the complexity of toddlers' utterances increases with their lexicon size (for a detailed discussion of the inter‐relatedness of lexicon and grammar throughout development, see Pérez‐Leroux et al, 2012). In addition, a recent study showed that HLE effects on toddlers' morphosyntax skills were mediated by their expressive vocabulary (DiCataldo & Roch, 2000). We addressed this possibility by examining potential mediation effects of LD over literacy beliefs associations with SU scores.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the literature indicates that the complexity of toddlers' utterances increases with their lexicon size (for a detailed discussion of the inter‐relatedness of lexicon and grammar throughout development, see Pérez‐Leroux et al, 2012). In addition, a recent study showed that HLE effects on toddlers' morphosyntax skills were mediated by their expressive vocabulary (DiCataldo & Roch, 2000). We addressed this possibility by examining potential mediation effects of LD over literacy beliefs associations with SU scores.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the HLE also has a bearing on the child's language and literacy development, particularly the availability of picture books (Burris et al, 2019) and children's reading material, and the activities undertaken by family members at home related to literacy learning (Dicataldo & Roch, 2022;Snow et al, 1998). The age at which children first have any contact with reading material is also thought to be important (Sénéchal, 2012;Storch & Whitehurst, 2002): early years reading has been found to encourage vocabulary gains that led to greater levels of reading and increased growth in word knowledge (Frumkin, 2013).…”
Section: Aspects Of the Home Literacy Environment (Hle)mentioning
confidence: 99%
“…Finally, beyond the world of books and the written word, the HLE also influences children's language development and oracy skills (Burgess et al, 2002). A rich and supportive home environment encourages more rapid and accurate acquisition of new words, greater phonological awareness, and a stronger understanding of the communicative potential of language (Dicataldo & Roch, 2022). Increased responsiveness from parents also proves beneficial for children's language learning (Landry et al, 2017), and the number of interactions children engage in with more knowledgeable caretakers has been found to be a central variable in language development (Romeo et al, 2018).…”
Section: Types Of Activitymentioning
confidence: 99%
See 2 more Smart Citations